Physical Fitness Level of Physical Education Students of Dehasen University, Bengkulu - Ritanza, Febra; Lismana, Oetari; Ferdiansah, Rahmad (Universitas Majalengka, 2024)
This study aims to determine the level of physical fitness possessed by physical education students at Dehasen University, Bengkulu. This study is a quantitative descriptive study using a survey method. The sampling technique used in this study is random sampling, which is a technique for taking samples from a population randomly and using the principle of probability in determining the sample elements. The subjects in this study were 249 students of the Physical Education Department, Dehasen University, Bengkulu, semester 3, class of 2023, and in determining the sample using the Slovin formula with an error rate of 20% which then got a result of 10.96 which was then rounded up to 11 samples. This study is a quantitative descriptive study that uses a survey method. In this study, the sampling technique used is random sampling, where the research sampling technique in this study was carried out randomly and used the principle of probability in determining the sample elements. This study in its data collection technique uses tests and measurements of the Indonesian Physical Fitness Level (TKJI) aged 16-19 years. The data analysis technique uses descriptive analysis which is then expressed in the form of percentage figures. Based on the results of the research that has been done, the results of the physical fitness level of physical education students at Dehasen University, Bengkulu were obtained. The assessment was based on 5 items of the Indonesian Physical Health Test, namely 30-meter sprint, Pull-UP, Sit-UP, Vertical, and the last was medium-distance running. The results of data analysis from the measurement test based on the TKJI calculation benchmark obtained data and values ​​which were then categorized into five categories, namely very good, good, moderate, less, and very less. Of the 11 students who received the Very Good category, there was 1 person, the Good category was 6 people, the Moderate category was 4 people, the Less category was 0 people, and the last category was the Very Less category was 0 people, and from the entire test sample, the average category was GOOD.